Culinary Behavior of Generation Z in Bengkulu City - Rina, Rina; Suminar, Panji; Himawati, Ika Pasca (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
This study examines culinary behavior among Generation Z in Bengkulu City by analyzing its associations with price perception, taste, restaurant location, social factors, and healthy lifestyle orientation. Employing an associative quantitative design, data were collected from 384 respondents selected through purposive sampling. The analysis was conducted using multiple linear regression. The findings indicate positive associations between culinary behavior and the examined predictors, with restaurant location and social factors showing the strongest standardized contributions in the model. Price perception and taste also demonstrate meaningful associations, suggesting that economic evaluation and sensory satisfaction remain central considerations in culinary decision making. Healthy lifestyle orientation shows a smaller association; however, because the regression diagnostics indicate heteroscedasticity related to this predictor, statistical inferences for this variable should be interpreted cautiously. These results suggest that culinary consumption among the surveyed Generation Z respondents represents a socially embedded practice shaped by the interaction of practical, experiential, spatial, and social dimensions. The coexistence of fast food and traditional cuisine preferences further reflects the adaptive and hybrid nature of Generation Z consumption patterns in a mid-sized urban context. Because purposive sampling was used, the findings are not intended for probabilistic generalization to all Generation Z residents in Bengkulu City.